2000
DOI: 10.1021/bi000648o
|View full text |Cite
|
Sign up to set email alerts
|

The Met99Gln Mutant of Amicyanin fromParacoccusversutus

Abstract: The axial copper ligand methionine has been replaced by a glutamine in the cupredoxin amicyanin from Paracoccus versutus. Dynamic and structural characteristics of the mutant have been studied in detail using UV/Vis, EPR, NMR, cyclic voltammetry, and isomorphous metal replacement. M99Q amicyanin is a blue copper protein with significant spectral and structural similarities to the other cupredoxins umecyanin, stellacyanin, and M121Q azurin. In addition, the functional properties of M99Q amicyanin, as reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 56 publications
10
46
0
Order By: Relevance
“…All the hyperfine shifted resonances follow a Curie temperature dependence, as observed in other Co(II)-substituted blue copper proteins [15,24,25,26,31,32,33,34,35,36,37]. Their chemical shifts and relaxation rates are typical of signals corresponding to proton nuclei from metal ligands ( Table 1).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…All the hyperfine shifted resonances follow a Curie temperature dependence, as observed in other Co(II)-substituted blue copper proteins [15,24,25,26,31,32,33,34,35,36,37]. Their chemical shifts and relaxation rates are typical of signals corresponding to proton nuclei from metal ligands ( Table 1).…”
Section: Resultssupporting
confidence: 63%
“…Resonances A and C are broader than the rest of the signals in the spectrum, and exhibit shorter T 1 values (Table 1). Based on these spectral features, we feel confident to assign A and C to the Cys78 b-CH 2 protons by analogy with similar assignments in other Co(II)-substituted cupredoxins [15,24,25,26,31,32,33,34,35,36,37].…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Site-directed point mutation of the axial ligand has been carried out for blue copper proteins. It has been reported that the replacement of Met at the axial ligand by Gln causes the negative shift in the formal potential of the type I Cu site in blue copper proteins [7][8][9][10][11]. In contrast, the replacement of Gln by Met causes the positive shift in the formal potential [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Azurin has been the topic of many such studies [5]. Amicyanin from P. versutus has also been studied and the effect of mutation of its axial Met ligand to Gln was examined [6]. In those studies the metal specificity and role of the metal during protein folding was studied by first denaturing the protein usually with guanidine HCl.…”
Section: Introductionmentioning
confidence: 99%